Factors influencing e-Procurement adoption in the Nigerian building industry (Construction Economics and Building, 2016)
Against the backdrop of increasing adoption of e-Procurement in supply chain management, there is a need for adequate knowledge of the factors that influence the decision by organizations in the building industry to use e-Procurement. This study aims to fill the knowledge gap through investigating the factors influencing e-Procurement adoption based on the data sourced in a questionnaire survey involving 213 organizations in the building industry. The survey was conducted between June and November 2015 in Nigeria. Descriptive statistics, factor and categorical regression analyses were used to analyze the data. The results show that the three most important factors influencing the adoption of e-Procurement amongst the participants, in order of importance, were: the benefits of e-Procurement in enhancing efficiency in project delivery; eliminating geographic barriers and effective communication among project team members. The 29 factors were investigated in seven different dimensions - the benefits of e-Procurement use; level of awareness on e-Procurement in construction; and the availability and cost of e-Procurement applications emerged as the three most significant predictors of e-Procurement adoption in the survey. The study concludes by identifying strategies that should be engaged in increasing the uptake and maximizing the benefits of e-Procurement in the Nigerian building industry.